"Victims' participation rights in the post-sentencing phase: The Netherlands in comparative perspective". Issue 2 (June 2021) - Bosma, Alice K.; Groenhuijsen, Marc S.; de Vries, Max
Victims' rights have proliferated rapidly over the past decades. However, the development of rights in the post-sentencing phase has lagged behind. In this article, we argue that victims' rights may contribute to the acknowledgement of victims, something that victimological research suggests is important for victims' well-being at every stage of criminal proceedings. We review a new Dutch law and a legislative proposal aiming to improve victims' rights in the post-sentencing phase in relation to conditional release from prison and conditional discharge from forensic psychiatric hospital. More specifically, we compare these (proposed) victims' participatory rights with those existing in the Canadian, Belgian and German framework. We argue for a strengthened position of the victim in the post-sentencing phase. We close by showing that the practical effectiveness of these proposed rights is put at risk by COVID-19 and states' response to the same.